(untitled) (Research, Society and Development, 2021)
This retrospective, observational, longitudinal study performed a morphometric analysis of the pterygopalatine fossa (PPF) in patients undergoing surgically assisted rapid maxillary expansion (SARME) using cone beam CT (CBCT). CBCT scans of 41 consecutive patients were assessed and the following measurements were performed: PPF volume (PPFV), height (PPFH), length (PPFL) and angle (PPFA). The sample was divided into groups D (patients undergoing SARME; n=26) and control (n=15). Group D was subdivided into D+ (with pterygomaxillary disjunction – PMD) and D- (without PMD). The differences between the pre and postoperative periods were tested using the U Mann-Whitney or the t-test. Groups D+ and D- were compared using the one-way ANOVA or Kruskal-Wallis tests (level of significance set at 5%). In general, there were morphometric variations in PPF, with lower values after SARME. Differences for PPFH, PPFL and PPFA were not significant (p>0.05). On the right side, there were differences in PPFV, with lower values in patients from group D+ (p<0.05). These findings indicate a morphometric reduction of PPF after SARME, with differences when the disjunction is performed or not. The maxillofacial surgeon must be aware of these changes when performing SARME with or without disjunction.